Potential chitosan-coated alginate nanoparticles for ocular delivery of daptomycin - Costa, J. R. (2016)
Daptomycin may offer an antibacterial alternative for the treatment of endophthalmitis caused by methicillin-resistant Staphylococcus aureus (MRSA) and other potential agents. In the present project, mucoadhesive chitosan-coated alginate (CS-ALG) nanoparticles are proposed as an effective delivery system for daptomycin permeation across ocular epithelia, with potential for the treatment of bacterial endophthalmitis. CS-ALG nanoparticles were prepared by ionotropic pre-gelation of an alginate core followed by chitosan polyelectrolyte complexation, and characterized regarding particle size, polydispersity, and zeta potential. The encapsulation efficiency was determined and antimicrobial activity was also tested after encapsulation of the antibiotic. Also, in vitro ocular permeability of free daptomycin and encapsulation into chitosan and CS-ALG nanoparticles was evaluated using ocular epithelial cell culture models. Formulated daptomycin-loaded CS-ALG nanoparticles were negatively charged, with a size range of 380–420 nm, suitable for ocular application. The encapsulation efficiency was between 79 and 92 %, with decreasing alginate:daptomycin mass ratios. The antibacterial activity of daptomycin against major microorganisms responsible for bacterial endophthalmitis was not affected by encapsulation into nanoparticles. Daptomycin permeability was up to 16 % (chitosan nanoparticles) and 9 % (CS-ALG nanoparticles) through corneal cell monolayer, and 18 % (chitosan nanoparticles) and 12 % (CS-ALG nanoparticles) for retinal cell monolayer after 4 h, demonstrating epithelial retention of the drug compared to free drug. The developed daptomycin-loaded CS-ALG nanoparticles seem to be an interesting and potential system for ocular daptomycin delivery and treatment of bacterial endophthalmitis.